Upaya Peningkatan Pemahaman Masyarakat Melalui Penyuluhan Tentang Pentingnya Imunisasi Dan Pemberian Makanan Tambahan (PMT) Pada Bayi Dan Balita - Irmayanti AR; Gusnawati, Yesi (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Immunization is one of the basic preventive health services aimed at reducing the infant mortality rate. It is also one of the most cost-effective health investments to prevent individuals from contracting infectious diseases, and is routinely provided to the community from infancy. Objective: In addition, broader immunization coverage and the provision of appropriate supplementary feeding (PMT) are expected to help reduce stunting rates, infectious diseases, and child mortality. Method: The purpose of this activity is to provide an understanding of the importance of immunization for children as well as the importance of proper supplementary feeding (PMT) in the village. Result: The method used in this activity was conducting a preliminary study. Conclusion: Increasing public awareness about immunization and the provision of supplementary food for infants and toddlers is essential for creating a healthy and strong generation.